PEMBINAAN KELUARGA MELALUI MEDIA WHATSAPP GROUP MENINGKATKAN KETAATAN PELAKSANAAN PROTOKOL KESEHATAN PENCEGAHAN COVID-19 - Hermawan, Ketut; Sukawana, I Wayan; Yasa, I Dewa Putu Gede Putra (Coping: Community of Publishing in Nursing; Vol 9 No 4 (2021): Agustus 2021, 2021)
Abstrct : The Influence Of Family Coaching Through WhatsApp Group Media On Adherence to COVID-19 Preventive Health Protocols. . This study aims to determine the effect of family coaching through the whatsapp group media on compliance with COVID-19 prevention health protocols. Respondents of this study were 30 family heads in Banjar Dinas Ketug - Ketug, Jinengdalem Village who were taken using simple random sampling technique. Data was collected by observing the behavior of adhering to the Covid-19 preventive health protocol. The results of this study found that there was an effect of family coaching through the WhatsApp group media on compliance with the COVID-19 prevention health protocol with r-value = 0.000 < alpha (0.05). %) The conclusion is that there is a change in the respondent's obedient behavior regarding the adherence to the COVID-19 prevention health protocol